Isolation and characterisation of milk-derived amyloid-like protein aggregates (MAPA) from cottage cheese. (30th March 2022) - Malik, Shweta; De, Indranil; Singh, Manish; Galanakis, Charis M.; Alamri, Abdulhakeem S.; Yadav, Jay Kant
Highlights: The production of cottage cheese involves heat treatment and acidification of milk. The cottage cheese contains amyloid-like protein aggregates. These milk derived protein aggregates (MAPA) are found to be non-toxic. Abstract: Cottage cheese, extensively consumed worldwide, contains coagulated milk protein (casein), produced through boiling and acidification of milk. Casein forms amyloid or amyloid-like structures at high temperatures and low pH. Due to the similarities in the preparation of casein amyloids and cottage cheese, we hypothesized the presence of amyloid or amyloid-like protein aggregates in cottage cheese. To examine this hypothesis, cottage cheese was prepared from cow ( Bos indicus ) milk and isolated amyloids through a water extraction method. The isolated protein aggregates displayed typical characteristics of amyloids, such as a bathochromic shift in the wavelength of maximum absorption (λmax ) of Congo red (CR), high thioflavin T (ThT) binding, increased surface hydrophobicity, and high β-sheet structure. However, they did not show antibacterial activity and toxic properties against erythrocytes. Our study revealed that the heat-treatment and subsequent acidification during cottage cheese preparation lead to the formation of non-toxic amyloid-like aggregates.